Determinant Factors of the Unemployment Rate in Banten Province - Feny Robingatun Khasanah; Grace Natalia Marpaung (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Every country strives to minimize the unemployment rate as much as possible. The Open Unemployment Rate in Banten Province, which has consistently been higher than the national average, has become a serious concern. This study aims to examine the influence of the labor force participation rate, economic growth, average years of schooling, and city minimum wage on the open unemployment rate in Banten Province during the 2017-2023 period. This research utilizes Eviews 12 software with a panel data approach, combining cross-sectional and time-series data over seven years, from 2017 to 2023. The method applied in this study is the Fixed Effect Model (FEM). The data analyzed in this study are secondary data obtained from the Central Statistics Agency (BPS) of Banten Province. The research findings indicate that the labor force participation rate, economic growth, and average years of schooling have a negative and significant effect on the open unemployment rate in eight districts/cities in Banten Province from 2017 to 2023. Conversely, the city minimum wage variable has a positive but insignificant effect. Additionally, the independent variables, namely the labor force participation rate, economic growth, average years of schooling, and city minimum wage, simultaneously have a significant effect on the dependent variable, which is the open unemployment rate in Banten Province during the 2017-2023 period, contributing 76.48% to the variation in the open unemployment rate in Banten Province.